Web development with TIBCO General interface : building Ajax clients for enterprise SOA - Gurnani, Anil (Developer's library., 2009)
Web Development with TIBCO General Interface Building AJAX Clients for Enterprise SOA Anil Gurnani Use TIBCO General Interface to build web applications with state-of-the-art performance and usability TIBCO General Interface provides powerful tools and a framework to craft AJAX-based web applications that rival desktop applications in performance and usability. This is the only book that offers developers thorough guidance for using TIBCO's award-winning open source tools to build interactive, high-performance GUIs and integrate them with leading server-side technologies. Experienced TIBCO General Interface developer Anil Gurnani focuses on applying General Interface in real-world production applications and presents numerous working examples that can easily be adapted for your existing sites and applications. You'll first walk through the fundamental concepts and techniques needed to build powerful General Interface clients. Next, you'll dive into specific back-end technologies, mastering them through start-to-finish case study projects. Finally, drawing on his own experience building enterprise-class General Interface applications for the financial services industry, Gurnani illuminates advanced topics ranging from charting and collaboration to application optimization. Coverage includes Integrating XML and XSL with TIBCO General Interface's XML Mapping utility Extending General Interface widgets with object-oriented JavaScript Integrating with web services, databases, portals, and messaging systems: start-to-finish case study sample applications Integrating General Interface applications into service-oriented enterprises using Enterprise Service Bus (ESB) Using OpenAJAX Hub (TIBCO PageBus) to simplify collaboration among GUI components Anil Gurnani's book greatly augments the available information for developers learning and using TIBCO's General Interface. ... With this book, you will quickly be building General Interface applications, faster and easier than ever before.-Michael Peachey, co-founder of General Interface and Director of User Experience, TIBCO Software Anil Gurnani has written extensively on technical topics for many prestigious magazines. He is an adjunct at SCPS, New York University, where he teaches advanced courses focused on web and enterprise technologies including Core Java, JEE, and .NET. He is also an expert at managing large, global, multifunctional teams to architect and build complex distributed systems with a portf ...